Hadrah Spirit as an Islamic Arts in the Land of Papua - Nur Saidah; Septy Nur Fadhilah (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
The Land of Papua is synonymous with a non-Muslim population, and it is not uncommon for some people to think that there is no Muslim community in Papua. This assumption is increasingly supported by the inauguration of the capital city of West Papua, Manokwari as a city of the Bible. But on the contrary, the fact is that Islam entered the land of Papua since 1512, even before the entry of other religions. Therefore, in this study research will be conducted regarding the popularity of hadrah art as an Islamic art in Papua which can be used as evidence of the rapid development of Islamic civilization in Papua today. The method used in this research is a qualitative approach. In collecting data using direct observation in the field, survey media in the form of questionnaires and by using literature studies on previous research. From the research results obtained, it can be concluded that the existence of hadrah arts in Papua, especially the city of Manokwari is currently very popular, this is indicated by the many hadrah competitions and festivals being held, the many sholawat majlis which involve hadrah music as accompaniment to the Prophet's sholawat verses, and even the existence of hadrah as an extracurricular activity in educational institutions. The presence of this research is expected to increase one's knowledge of the development of Islam in the land of Papua, one of which is in the field of hadrah art as an Islamic art.